Cryopreserved clumps of mesenchymal stem cell/extracellular matrix complexes retain osteogenic capacity and induce bone regeneration - Souta Motoike; Mikihito Kajiya; Nao Komatsu; Manabu Takewaki; Susumu Horikoshi; Shinji Matsuda; Kazuhisa Ouhara; Tomoyuki Iwata; Katsuhiro Takeda; Tsuyoshi Fujita; Hidemi Kurihara (Stem Cell Research & Therapy, 2018)
Abstract Background Three-dimensional (3D) cultured clumps of mesenchymal stem cell (MSC)/extracellular matrix (ECM) complexes (C-MSCs) consist of cells and self-produced ECM. C-MSCs can regulate cellular functions in vitro and can be grafted into a defect site without an artificial scaffold to induce bone regeneration. Long-term cryopreservation of C-MSCs, which can enable them to serve as a ready-to-use cell preparation, may be helpful in developing beneficial cell therapy for bone regeneration. Therefore, the aim of this study was to investigate the effect of cryopreservation on C-MSCs. Methods MSCs isolated from rat femurs were cultured in growth medium supplemented with ascorbic acid. To obtain C-MSCs, confluent cells that had formed on the cellular sheet were scratched using a micropipette tip and were then torn off. The sheet was rolled to make a round clumps of cells. The C-MSCs were cryopreserved in cryomedium including 10% dimethyl sulfoxide. Results Cryopreserved C-MSCs retained their 3D structure and did not exhibit a decrease in cell viability. In addition, stem cell marker expression levels and the osteogenic differentiation properties of C-MSCs were not reduced by cryopreservation. However, C-MSCs pretreated with collagenase before cryopreservation showed a lower level of type I collagen and could not retain their 3D structure, and their rates of cell death increased during cryopreservation. Both C-MSC and cryopreserved C-MSC transplantation into rat calvarial defects induced successful bone regeneration. Conclusion These data indicate that cryopreservation does not reduce the biological properties of C-MSCs because of its abundant type I collagen. More specifically, cryopreserved C-MSCs could be applicable for novel bone regenerative therapies.